Humanities in Sweden: Heroes or Servants? - Voidogienė, Eglė (Respectus Philologicus, 2019)
[full article and abstract in Lithuanian; abstract in English]The aim of this research is to analyse the legitimacy problem of the humanities in Sweden. The first part presents the analysis of the arguments for the humanities published in relevant studies, anthologies as well as articles in the most popular cultural and academical magazines in Sweden from 2004 to 2014. The method was based on the Grounded Theory’s elements and had three steps. The result was four big categories of the arguments which also reflected four concepts of the humanities that were prevailing in Sweden. 1) Civic humanities. The authors argued that the humanities are necessary in order to build a democratic society and educate citizens who would be able to think critically and act responsibly. This group of argumentations was the biggest and the most popular. 2) Heroic humanities. It was claimed that the humanities are necessary to face the most serious challenges, globalization, homophobia, Islamophobia, climate change etc. 3) Integrative humanities that are considered as most valuable when they collaborate with other disciplines. 4) Existential humanities. According to this group, the humanities are most valuable when they raise the existential questions. The second part presents a short analysis of the programs of political parties from the year 2018. Although the legitimacy problem of the humanities has not taken a bigger part there, we can find links to all four concepts.
Keywords: humanities; Sweden